Healing Childhood Psychological Trauma and Improving Body Image Through Cosmetic Surgery - Ip, Ka Tung Vivianne; Ho, Wing Yee (Frontiers in Psychiatry, 2019)
Cosmetic surgery is an interdisciplinary field involving cosmetics and medicine that stems from the early modern obsession with disfigurement. The “correcting” of facial features and body parts was very likely because beauty was at the heart of most reconstructive desires. Cosmetic surgery patients typically experience improvements in body image, and some are very satisfied with the impact of cosmetic surgery in changing their behaviors and improving self-esteem. The doctrine of mind–body connection supports the concept of healing the heart through the body. However, some people feel disgraced after revealing their experiences of cosmetic surgery. It is known that people who experience childhood psychological trauma, such as abuse and school bullying, may opt for cosmetic surgery later in life. The present study aimed to explore the relationship between childhood psychological trauma, cosmetic surgery, and body image. Three female adults who had undergone different types of cosmetic surgery completed the Acceptance of Cosmetic Surgery Scale (ACSS), the Fear of Negative Appearance Evaluation Scale (FNAES), and the Multidimensional Body-Self Relations Questionnaire (MBSRQ), followed by semi-structured face-to-face interviews. According to the results, (1) undergoing cosmetic surgery can enhance self-confidence, reduce body dissatisfaction, resolve inner conflicts, and somewhat relieve psychological distress; (2) self-esteem and body image obtained from cosmetic surgery can resolve the distressing aftereffects of childhood trauma that occur later in life; and (3) the perceived sense of beauty achieved from cosmetic surgery contributes to a certain degree of self-confidence in the short term and promotes appearance-enhancing behaviors while increasing the distress of others discovering their cosmetic surgery experiences. The implications of this study are that undergoing cosmetic surgery can have healing effects on childhood trauma; however, there are certain drawbacks that can occur, such as distress and an insatiable desire for or an “addiction” to surgery.